2021
DOI: 10.3389/fpubh.2021.606666
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Healthcare Providers Toward Novel Coronavirus 19 During the First Months of the Pandemic: A Systematic Review

Abstract: Introduction: Coronavirus disease (COVID-19) is a highly contagious viral infection that has spread to every corner of the world. Lack of knowledge among healthcare providers (HCPs) about diseases such as COVID-19 may delay the diagnosis, disease spread, and produce poor infection control practices. Hence, this systematic review aimed to summarize the knowledge, attitudes, and practices (KAP) of HCPs toward COVID-19 during the first months of the pandemic.Methods: A systematic review was conducted according th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
4
15
1
Order By: Relevance
“…A study in Nepal found that 76% of HCWs reported adequate knowledge, 54.7% reported positive attitudes, and 78.9% reported behavioral practices; here, knowledge was positively associated with attitudes and practices (19). A global systematic review with 20 studies including 12,072 HCWs reported a 75.8% had good knowledge, 74.6% had positive attitudes, and 79.8% had good practices toward COVID-19 (15). Based on this literature and the evolving COVID-19 scenario, it is still necessary to identify the coronavirus's KAP among HCWs.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A study in Nepal found that 76% of HCWs reported adequate knowledge, 54.7% reported positive attitudes, and 78.9% reported behavioral practices; here, knowledge was positively associated with attitudes and practices (19). A global systematic review with 20 studies including 12,072 HCWs reported a 75.8% had good knowledge, 74.6% had positive attitudes, and 79.8% had good practices toward COVID-19 (15). Based on this literature and the evolving COVID-19 scenario, it is still necessary to identify the coronavirus's KAP among HCWs.…”
Section: Introductionmentioning
confidence: 96%
“…In Bangladesh, the mortality rate of HCWs was relatively low (0.05 per 100,000 population); however, these data don't accurately portray the actual scenario since testing capacity and research data were inadequate (14). Studies revealed that HCWs' lack of knowledge and misconceptions may have led to delays in diagnosis and poor infection prevention practices (11,15). Experience gained from the previous Severe Acute Respiratory Syndrome (SARS) outbreak in 2003 revealed that inadequate knowledge, negative attitudes, and poor behavioral practices (KAPs) regarding infectious diseases impeded containment and inhibited further transmission (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, the severity and rapid transmission of COVID-19 overloaded the HCWs weakening the established infection prevention and control (IPC) across many health settings [ 5 ]. Despite the high observed rate of the knowledge, attitude, and practices of HCWs towards COVID-19 containment compared to other communities, the overloaded working environment with the shortage of PPE made HCWs more vulnerable to COVID-19 infection [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the level of education is positively correlated with the individual's cognitive level and knowledge learning ability [e.g., (35)(36)(37)]. The higher the level of education, the easier it is to accept the technical products represented by digitization.…”
Section: Producer Knowledge Level (Produ_edu) and Consumer Knowledge Level (Consu_edu)mentioning
confidence: 99%